THE SPECIFICITY OF GUO WENJING’S MUSICAL STYLE (ON THE EXAMPLE OF THE OPERA «POET LI BAI») - Hnatiuk, Daria (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
Relevance of the study. In the contemporary globalized civilizational space, established cultural and spiritual-practical stereotypes acquire symbolic functions. The conscious artistic reinterpretation of folklore within the framework of modern stylistics has become one of the most characteristic features of Chinese composers of the late 20th and early 21st centuries. A special place in their creative explorations is occupied by the operatic genre. The creative output of the representatives of this trend, particularly Guo Wenjing’s opera Poet Li Bai, defines the trajectory of the development of Chinese opera and introduces new aesthetic concepts into the existing vocabulary of Western theatrical-dramaturgical models, which determines the relevance of the present study. Main objective of the study is to explore the specificity of the creative method underlying Guo Wenjing’s individual style, using the opera Poet Li Bai as an example. Methodology includes the following methods: analytical, comparative, cultural and interpretive. Results and conclusions. Factors of mental origins and the neo-folkloristic orientation of Guo Wenjing’s compositional style are identified. On the example of Guo Wenjing’s opera Poet Li Bai, it is demonstrated how profound philosophical concepts and artistic principles of traditional Chinese art acquire a new form of existence within contemporary musical drama, becoming the basis of dramaturgical solutions and multifaceted metaphorics at the levels of the character system, musical language, and stage interaction. It is established that the dramaturgical structure of the opera Poet Li Bai relies on the mosaic principle, which creates a multidimensional image of the artist. Such a model allows the opera to be interpreted not as a linear illustration of historical events but as an artistic reflection on the spiritual path and creative identity of Li Bai. Through the analysis of the stage embodiment of three key images — Moon, Wine, and Poetry — in their interaction with the protagonist, the mechanisms of the alienation effect, used by Guo Wenjing as the basis of the dramaturgical composition of the opera, are identified and substantiated. It is traced how abstract ideas are embodied in concrete stage forms, enter into dialogue with the poet, and return to the symbolic sphere, creating a complex system of communicative relations between stage and audience. It is revealed that the manifestation of cyclicity, one of the fundamental categories of Eastern philosophy, attains the status of a key structural principle of the composition. On the basis of the analysis, the specific traits of Guo Wenjing’s musical style are defined, which consist in the avoidance of academic clichés, the constant striving for creative renewal, the active use of the symbolic nature of intonations, and the aspiration for a profound disclosure of the inner world of the protagonist.